2004
DOI: 10.1086/380817
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Rising Hydrodynamic and Magnetohydrodynamic Bubbles from Numerical Simulations

Abstract: Recent Chandra and XMM-Newton observations of galaxy cluster cooling flows have revealed X-ray emission voids of up to 30 kpc in size that have been identified with buoyant, magnetized bubbles. Motivated by these observations, we have investigated the behavior of rising bubbles in stratified atmospheres using the Flash adaptive-mesh simulation code. We present results from 2-D simulations with and without the effects of magnetic fields, and with varying bubble sizes and background stratifications. We find pure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 44 publications
3
100
1
Order By: Relevance
“…First, our simulations include magnetic fields, while theirs are purely hydrodynamic. As a result, the AGN bubbles in our simulations in general keep their integrity for longer periods of time, reach to further distances, and mix with the ambient ICM more slowly, because of the suppression of hydrodynamic instabilities by magnetic tension at the surface of the bubbles (e.g., Robinson et al 2004). Because it is more difficult for the bubbles to couple with the ICM, in general a lower feedback efficiency ò (thus a smaller radius of influence and higher thermalization efficiency) needs to be used in the MHD simulations in order to generate similar profiles to thosein hydrodynamic simulations.…”
Section: Comparisons With Previous Workmentioning
confidence: 92%
“…First, our simulations include magnetic fields, while theirs are purely hydrodynamic. As a result, the AGN bubbles in our simulations in general keep their integrity for longer periods of time, reach to further distances, and mix with the ambient ICM more slowly, because of the suppression of hydrodynamic instabilities by magnetic tension at the surface of the bubbles (e.g., Robinson et al 2004). Because it is more difficult for the bubbles to couple with the ICM, in general a lower feedback efficiency ò (thus a smaller radius of influence and higher thermalization efficiency) needs to be used in the MHD simulations in order to generate similar profiles to thosein hydrodynamic simulations.…”
Section: Comparisons With Previous Workmentioning
confidence: 92%
“…Although in two dimensions magnetic fields act to stabilize some instabilities (e.g., Robinson et al 2004), in three dimensions the magnetic fields cannot suppress instabilities with wave-vector components perpendicular to the field lines. Hence, we do not expect magnetic fields to suppress mixing, but only to influence the details of the mixing.…”
Section: Numerical Setupmentioning
confidence: 99%
“…While it has been common to conduct bubble stability studies beginning with static, pre-formed bubbles (e.g., Robinson et al 2004;Ruszkowski et al 2007), instead Jones & De Young (2005) gently "pressure inflated" their bubble structures over a period of at least 10 Myr during their simulations. Since real relic bubbles are not created instantaneously, they argued that relevant stability issues, including magnetic field geometries, may be sensitive to that fact.…”
Section: The Bubblesmentioning
confidence: 99%
“…Hydrodynamic simulations conducted by Kaiser (2001) in 2D andBrüggen et al (2002) in 3D confirmed the anticipated timescales of ∼ 10 7 years for disruption from hydrodynamical instabilities in such bubbles. To explore the effects of magnetic fields on bubble dynamics and stability, Robinson et al (2004) and Jones & De Young (2005) conducted multiple series of 2D magnetohydrodynamic (MHD) simulations involving relatively homogeneous ambient magnetic fields with a variety of field orientations with respect to the cluster gravitational field. Once again the bubble rise times were ∼ 10 8 years.…”
Section: Introductionmentioning
confidence: 99%